Thymic Regulatory T Cell Development: Role of Signalling Pathways and Transcription Factors - Mark Engel; Tom Sidwell; Ajithkumar Vasanthakumar; George Grigoriadis; Ashish Banerjee (Clinical and Developmental Immunology)
Regulatory T cells (Tregs) are a subset of CD4 T cells that are key mediators of immune tolerance. Most Tregs develop in the thymus. In this review we summarise recent findings on the role of diverse signalling pathways and downstream transcription factors in thymic Treg development.